1987
DOI: 10.1007/bf01200415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on development and growth in the tick,Haemaphysalis longicornis

Abstract: As a part of ecological studies on Haemaphysalis longicornis, the effects of controlled temperatures (12, 15, 20, 25 and 30 degrees C; approximately 100% RH) on development and growth of the tick were investigated and the critical low temperature for each stage in the life cycle was estimated. As the temperature became low, the periods of preoviposition, oviposition, egg hatching (incubation) and moulting were prolonged. At 12 degrees C, however, oviposition, egg hatching and moulting of the larva and nymph di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 4 publications
4
39
0
Order By: Relevance
“…Its complete life cycle requires a mean duration of 109.6 days, which is longer than those fed on Rattus fuscipes (Waterhouse) at condition of 27°C and 95% RH (72 days) (Doube and Kemp 1979). This discrepancy in life cycle period may be due to different temperature (Yano et al 1987), humidity (Despins 1992;Perret et al 2004), and host (Labruna et al 2002) among other ecological factors (Troughton and Levin 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Its complete life cycle requires a mean duration of 109.6 days, which is longer than those fed on Rattus fuscipes (Waterhouse) at condition of 27°C and 95% RH (72 days) (Doube and Kemp 1979). This discrepancy in life cycle period may be due to different temperature (Yano et al 1987), humidity (Despins 1992;Perret et al 2004), and host (Labruna et al 2002) among other ecological factors (Troughton and Levin 2007).…”
Section: Discussionmentioning
confidence: 94%
“…The plausible explanation is that field conditions are more complicated and the complex interplay among photoperiod, temperature, relative humidity as well as some other ecological factors affects the development of the ticks (Fourie and Horak 1994;Padgett and Lane 2001;Labruna et al 2002). For example, low temperature has been shown to prolong the durations of egg hatching, molting, preoviposition and oviposition of H. longicornis (Yano et al 1987) possibly due to attenuated metabolic rate at low temperature (Jiang and Bai 1989). Moreover, the appearance in Ixodes rubicundus and Anocentor nitens has been also observed, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…1), respectively. Since the fecundity appeared to be almost complete if the temperature was over 20°C (Yano et al 1987), lower temperature must be a responsible reason for the low fecundity. However, additional studies are required to further detail the development and reproductive preference of H. longicornis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors can also influence the timing of the life cycle. For example, Yano et al (1987) showed that when temperatures were low, engorged Haemaphysalis longicornis females took a longer time to lay eggs, and larvae and nymphs took longer to moult.…”
Section: Physiology and Behaviour Of Ticksmentioning
confidence: 99%